Pelatihan Pemanfaatan Kotoran Sapi sebagai Pupuk Organik - Esti, Risma Novela; Samur, Salnan Irba Novaela (Universitas Islam Balitar, 2024)
The allocation of subsidized fertilizer has significantly decreased compared to the amount proposed by the local government, due to the global increase in fertilizer prices. On the other hand, some farmers in Gedog Village have livestock, particularly cattle, but the manure from these animals has not been optimally utilized. Therefore, there is a need for training on composting cattle manure. The purpose of this training is to provide farmers and livestock owners with the knowledge and skills to process cattle manure into beneficial compost. The implementation method of this activity includes socialization and hands-on practice in managing cattle manure waste. The results of this community service activity through training show an increase in public awareness of the importance of processing cattle manure into compost. The process of producing organic fertilizer has yielded positive results, in line with expectations.